2016
DOI: 10.1016/j.renene.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Wave farm flicker severity: Comparative analysis and solutions

Abstract: This paper proposes a flicker severity study for Wave Energy Converter farms. The flicker severity is introduced and the reason why it is an important constraint for a wave farm is explained. A new representation called intrinsic flicker severity is introduced which describes the flicker severity independently of the grid. The influence of device type, its control and the sea-state on average production, flicker severity and on the ratio between flicker and production are studied with three types of devices: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…By arranging the park layout such that the WECs are not excited simultaneously by the incident waves, the power output can be further smoothened (Engström et al, 2013;Sjolte et al, 2013;Göteman et al, 2014). Armstrong et al (2015), Kovaltchouk et al (2016), and Blavette et al (2016) used approximate methods for hydrodynamics and power production in the array to study flicker severity with a focus on transmission and grid aspects. The impact of a park consisting of ten OWCs and ten heaving buoys on the transmission system was studied by Armstrong et al (2015), and it was concluded that the transformers and transmission lines would remain below 45% capacity.…”
Section: Delivering Grid-compatible Electricitymentioning
confidence: 99%
See 1 more Smart Citation
“…By arranging the park layout such that the WECs are not excited simultaneously by the incident waves, the power output can be further smoothened (Engström et al, 2013;Sjolte et al, 2013;Göteman et al, 2014). Armstrong et al (2015), Kovaltchouk et al (2016), and Blavette et al (2016) used approximate methods for hydrodynamics and power production in the array to study flicker severity with a focus on transmission and grid aspects. The impact of a park consisting of ten OWCs and ten heaving buoys on the transmission system was studied by Armstrong et al (2015), and it was concluded that the transformers and transmission lines would remain below 45% capacity.…”
Section: Delivering Grid-compatible Electricitymentioning
confidence: 99%
“…The impact of a park consisting of ten OWCs and ten heaving buoys on the transmission system was studied by Armstrong et al (2015), and it was concluded that the transformers and transmission lines would remain below 45% capacity. Kovaltchouk et al (2016) studied limits to voltage fluctuations for arrays of different WEC types, and compensatory actions were proposed to allow grid integration. Blavette et al (2016) estimated the flicker level as a function of grid impedance angle.…”
Section: Delivering Grid-compatible Electricitymentioning
confidence: 99%
“…The MaRINET report on demand side grid compatibility offers methods for designing control systems and array layouts to meet grid codes [169]. Flicker is a measure of voltage fluctuations which is impacted by the WEC farm size and architecture, device type, control, and sea state [170]. Although the impacts of flicker depend on the grid strength [171], Kovaltchouk et al present a method of evaluating flicker independent of the grid [170].…”
Section: Grid Integrationmentioning
confidence: 99%
“…Flicker is a measure of voltage fluctuations which is impacted by the WEC farm size and architecture, device type, control, and sea state [170]. Although the impacts of flicker depend on the grid strength [171], Kovaltchouk et al present a method of evaluating flicker independent of the grid [170]. Blavette et al point out that because site-specific grid compatibility studies are time consuming and require a lot of detail, developers often put them off.…”
Section: Grid Integrationmentioning
confidence: 99%
“…However, they help to determine whether more detailed flicker level assessment studies need to be performed. Another work has focused on developing an intrinsic flicker severity index independent of both the short-circuit ratio and of the grid impedance angle [12]. However, this paper assumed that electrical lines are lossless, which can lead to a significant error level when sufficiently resistive networks, as it is the case in distribution networks, are considered.…”
Section: State Of the Artmentioning
confidence: 99%